Percepções do suicídio em uma força de segurança pública brasileira: um estudo de caso - Strauch, Allan Georges Nakka (2022)
This research aims to analyze the suicide in a Brazilian public security force (FSP) through empirical perceptions, based on a case study. In this sense, questionnaires (121 questions) were applied to 100 FSP police officers, which allowed obtaining a confidence level of 90%, with a margin of error of 6%. The treatment of these data focused on analysis by frequency distribution of responses and econometric treatment through logistic regression. The dependent variable considered the fact that “the FSP police officer had already thought about and/or attempted suicide” versus “never thought about or attempted suicide”. As main results, 49% have already thought about suicide, 6% have already attempted suicide (sum of 55%), while 45% have never thought about this act. The variables “family member committed suicide” (family characteristics), “happiness high” and “had depression” (health characteristics), “thought of shooting people” and “distress due to pressure at work” (temperament characteristics), “wanted to be a FSP police officer”, “moral harassment”, “met an FSP police officer who died on duty/work” and “friend of FSP police officer who committed suicide” (work characteristics) were statistically significant. Such variables explain, econometrically, the FSP police officer having thought and/or attempted suicide. These results suggest that the Institution A needs to institute mental health campaigns, as well as suggesting that qualified treatments be implemented to care for people who presented suicidal thought(s), with cases of attempts to take one's own life.